"I SE HAN SAJADO LAS CARNES": feminine sexuality and cosmist enunciation in Ande by Alejandro Peralta - Mondoñedo Murillo, Marcos (2021)
This paper aims at demonstrating that the textual significance of Alejandro Peralta’s collection of poems Ande (1926) includes a poetic configuration that is homologous to the poetic and political strategy of the indigenist avantgardism of the Orkopata group. For this purpose, we use the categories of the «semiotics of practices» developed by Jacques Fontanille and the concept of «cosmism». These categories allow us to outline a tension, proper to the instance of the enunciation of the poetry book, between the respectfor the strategic guidelines of the group and its critical questioning. This is so because, although there is a correspondence between poetics and political project, the theme of female sexuality in the collection breaks with this utopian harmonization and makes visible a divided enunciative subjectivity that, on the one hand, is in solidarity with the group’s proposal, but on the other hand, cannot deal with what for him is an ungovernable anomaly, that of female jouissance.